Italian Think Tanks in the Context of European Conservatism - Natalya V. Davletshina; Ulyana A. Zhegalova (Научно-аналитический вестник Института Европы РАН)
This article examines the influence of conservative think tanks on the integration of right-wing forces in Italy and the countries of the European Union, and how such centres participate in the ideological development of Europe. It also analyses the trend towards the «Europeanisation» of the activities of national centres and foundations due to the increasing centralisation of power in Brussels and the influence of supranational institutions. On the basis of each European party there is an think-tank which collaborates with ideologically close national organisations. Recently, Italy has shown a growing influence of right-wing and right-populist forces. In 2022 the leader of the extreme-right party «Brothers of Ital» Giorgia Meloni was elected as Prime Minister, and the majority of seats in the Italian Parliament are also held by politicians from right-wing parties. The «Brothers of Italy» have several think-tank centres, which are engaged in cooperation with representatives of conservative forces from different countries of the European Union, development of ideology and education of young politicians to form the future governing class. The article uses concrete examples to examine how the creation of a conservative political network in the EU is organised and what place Italy takes in it.